Analisis SWOT dalam implementasi sistem manajemen mutu ISO 9001:2008 di Sekolah Menengah Kejuruan Muhammadiyah 3 Yogyakarta tahun 2013/2014 - Sumadi Sumadi (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aimed to describe the analysis of Strength, Weakness, Opportunities, Threat (in education can be interpreted challenge) in the implementation of QMS ISO 9001: 2008 in the Vocational High School Muhammadiyah 3 Yogyakarta on 2013/2014 years in the element of planning (plan), implementation (do), evaluation (check) and follow-up (action) as a strategic move schools in continuous improvement efforts. This study used a qualitative approach, where the researcher as the key instrument. This study was conducted at Vocational High School Muhammadiyah 3 Yogyakarta in July 2013 - June 2014, the data source of this research is the principal, vice principal, team management and documentation. Data analysis using descriptive qualitative analysis, checking the validity of the data by triangulation with the source through in-depth interviews with other sources and focus group discussion and triangulation theory to the mandatory requirements of QMS ISO 9001: 2008. The results showed that the SWOT analysis in the implementation of QMS ISO 9001: 2008 in Vocational High School Muhammadiyah 3 Yogyakarta in 2013/2014 at the stage of growth strategies that have a great opportunity and the power to evolve towards better. PDCA element of the implementation of QMS ISO 9001: 2008 each have strengths, weaknesses, opportunities and threats or challenges that can be utilized for continuous improvement efforts Vocational High School Muhammadiyah 3 Yogyakarta. The strategy must be based on a SWOT analysis is a concentration on the quality of learning, promotion and distribution of market expansion, product development (excellent program), horizontal integration, vertical integration, concentric diversification, and conglomerate through.